Relationship between negative symptoms, cognitive function and social function in schizophrenia: new insight from a network analysis - Renliang Cai; Zaochen Zhu; Zaochen Zhu; Yan Li; Jin Fang; Chaoran Wu; Yunshan Hu; Shaotong Zhang; Chao Zhou; Xiandong Yang; Xinyu Fang; Xiangrong Zhang (Frontiers in Psychiatry)
ObjectiveThis study aimed to investigate the complex relationships between negative symptoms, cognitive function, and social functioning in chronic male patients with schizophrenia, identifying core symptoms to lay a theoretical foundation for targeted interventions aimed at negative symptoms in this population.MethodsA total of 161 male schizophrenia patients were included, categorized into deficit syndrome (DS) and non-DS groups using the Chinese version of the Schedule for the Deficit Syndrome (SDS). Social functioning was assessed with the Scale of Social Function in Psychosis Inpatients (SSPI), while a battery of neurocognitive tests measured cognitive domains, including sustained attention, cognitive flexibility, ideation fluency, and visuospatial memory. Network analysis was employed to construct an integrated network of negative symptoms, cognitive function, and social functioning, aiming to identify the most central and bridge symptoms within these networks.ResultsOur study indicated that DS patients performed worser in cognitive function and social functioning than non-DS patients. The network analysis demonstrated that “intensity of pleasure during activities (B1)” in the negative symptoms was the most central node. The most prominent bridge node was SSPI, with impact indices of 0.55.ConclusionOur findings provided evidence revealing a closer connection between negative symptoms, cognitive function, and social functioning. In light of these findings, precise targets for pharmacological treatment, psychotherapy and physical therapy are identified for patients with schizophrenia.